(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Diabetic Mellitus is a leading etiology of renal failure globally. About 20% to 40% of patients with diabetes tend to develop diabetic nephropathy. DPP-4 inhibitors and SGLT-2 inhibitors are quite helpful medications for Diabetic Nephropathy. Remogliflozin etabonate (RE) is a recent addition to the SGLT-2 inhibitor group for the management of type 2 diabetes mellitus (T2DM). Objective: The present study was conducted to describe the effects of the combination of SGLT-2 inhibitors and DPP-4 inhibitors in comparison to the combination of sulphonylureas and metformin on patients with diabetic nephropathy in T2DM. Study design: a randomized controlled trial Place and Duration: This study was conducted in the Primary and Secondary Healthcare Department, MOH, Kuwait, from January 2022 to January 2023. Methodology: The study includes a total of 104 patients with type 2 DM and diabetic nephropathy. The patients have been divided into two groups, i.e., Group A and Group B. Group A was given glimepiride 1 mg twice daily and metformin 500 mg twice daily. Group B was given SGLT-2 inhibitors (remogliflizone 100mg) twice daily and DPP-4 inhibitors (vildagliptin 50 mg) twice daily. A total of 52 patients were allotted to group A, and 52 patients were allotted to group B. The urine ACR, creatinine, and eGFR of all the patients were measured at the time of screening, the 12th week, the 24th week, and the 36th week of initiation of treatment. Results: The mean ACR of urine in the patients in Group A was 93.54 at the time of screening before starting the treatment, 95.78 at the 12th week, 89.85 at the 24th week, and 90.8 at the 36th week of treatment. The mean ACR of urine in the patients in Group B was 108.17 at the time of screening, 100.42 at the 12th week, 99.68 at the 24th week, and 75.02 at the 36th week of treatment. The mean eGFR in Group A at screening was 59.51; it was 61.3 in the 12th week, 60.3 in the 24th, and 60.7 in the 36th week. The mean eGFR in Group B at the screening was 68.02; it was 65.7 in the 12th week, 66.17 in the 24th, and 68.1 in the 36th week. Conclusion: The vidagliptin and Remogliflozin combination is helpful in a significant reduction in proteinuria and has shown improvement in eGFR compared to the combination of glimepiride and metformin.